Understanding Modern Food Insecurity in the United States Through a Historical and Political Analysis - Zervos, Konstantinos (Advances in Social Sciences Research Journal, 2025)
Despite advancements in quality of life and technology throughout the world, food insecurity has remained a challenge, consistently plaguing all nations. In the United States, modern food insecurity began during the Great Depression as the government introduced the first federal food program to moderate national economic hardship. Federal intervention in food insecurity soon became a hot topic for the next century as lawmakers debated federal policy shaping the landscape of food insecurity. This paper examines food insecurity through the dimensions that shape its current landscape: national and statewide politics, geography, and social inequality. Through this examination, this paper demonstrates that food insecurity presents a deep issue that can be categorized by a series of structural challenges, such as political polarization, geographic inequalities, and persistent racial and social disparities. This paper concludes by offering a solution to the modern problem of food insecurity by focusing on long-term solutions instead of following the contemporary model.